Effects of Mulligan’s Bent Leg Raise Technique on Hamstring Flexibility and Lumbar Spine Mobility in Healthy Females - Afia Irfan, Rafia Mannan, Aleena, Saima Riaz, Sajid Rashid, Rehan Ramzan Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To assess the effects of Mulligan’s bent leg raise technique on hamstring flexibility and lumbar spine mobility in healthy females. Methodology: A randomized controlled trial with ClinicalTrials.gov ID: NCT04716205 was conducted. The 48 participants were split into two groups. Mulligan’s bent leg raise (BLR) technique and static stretching were given to the experimental group, while only static stretching was given to the control group. The outcome variables were modified Schober’s (MST) and active knee extension tests (AKET). The assessment was completed at the outset, and post-treatment values were obtained after the first and second weeks of therapy. Results: Mean value of MST in the Control group pre-treatment was 3.27±0.33 and 4.11±0.37 at 1st-week post-treatment and 4.81±0.32 at the 2nd-week post-treatment, which was less significant than the experimental group. The findings revealed that the experimental group had significantly higher mean values for both the active knee extension test and the modified Schober’s test than did the control group. Conclusion: This research concluded that Mulligan’s bent leg raise technique combined with static stretching is more effective than static stretching alone in treating hamstring flexibility and spinal mobility. Keywords: Hamstring tightness, Mulligan BLR, Static stretching, flexibility